أثر الضبــط الإداري في ظــل جـــائحة كوفيد 19 على الحقوق و الحريات - هاشم, خديجة; عباس, صليحة شنيبة; هاشم, مروة (University of Eloued جامعة الوادي, 2022)
الضبط الإداري عبارة عن جملة من الأوامر والنواهي التي تفرضها السلطة على الأفراد وتكون ملزمة بهدف تنظيم حرياتهم، إلا أن هذه الأوامر والنواهي من شأنها تقييد الحريات العامة للأفراد حفاظا على النظام العام بعناصره الثلاث، حيث يشكل هذا الأخير الإطار العام الذي تتحرك فيه سلطات الضبط الإداري، وبذلك فحريات الأفراد تمارس في هذا الإطار تفاديا للفوضى التي تؤدي إلى انتكاسها، إلا أن الصلاحيات الممنوحة لسلطات الضبط الإداري بموجب لوائح الضبط من شأنها أن تأثر سلبا على حريات الأفراد، خاصة في ظل الضروفالإستثنائية نتيجة لتوسيع صلاحياتها لمواجهة الخطر الداهم الذي يهدد كيان الدولة والمجتمع. تتجسد فكرة الضبط الإداري في وباء كورونا"كوفيد 19"،ونظرا لخطورة هذا الوباء تضافرت الجهود الدولية لحماية الأفراد من الناحية الصحية، وكذلك حمايةحقوقهم وحرياتهم بضمان عدم تعسف سلطات الدول في الإجراءات والقيود التي إتخذتها، ولم يغفلالمشرع الجزائري أيضا على وضع ضمانات دستورية وأخرى قانونية من أجل حماية حقوقهم وحرياتهم. The admistrativewntrol is a wollection of orders and forbiddem things whieh. Imposed by the authoritiés and it is obliged to weryone so as to organize their liberties but these orders and forbidden things limit the public liberties to the to the individuals. To protect the public system in its three ways, this latter embrace the administrative control. That’s why the individual liberties is practised in this side in order to avoid the noise which leads to its relapse. However the given powers to the administrative control autborities under the administrative control rules which will negatively influence on the indiaidual liberties especially in this exptional circumstances as a result of enlarging its pouers to face the imminent danger which threatens state entity. The idea of administrative control is embodied in the Corona epidemic Covid 19, and given the seriousness of this epidemic, international efforts have joined forces to protect individuals in terms of health, as well as to protect their rights and freedoms by ensuring that the state authorities are not arbitrary in the procedures and restrictions they have taken, and the Algerian legislator also did not neglect the establishment of constitutional and other guarantees. legal in order to protect their rights and freedoms
مذكرة ماستر
Keywords: الضبط الإداري، الظروف الاستثنائية، الحقوق والحريات، النظام العام، كوفيد 19.; Administrative control, Exceptional circumstances, Rights and freedoms, public order, Covid 19.